Threshold increase and lasing inhibition due to hexagonal-pyramid-shaped hillocks in AlGaN-based DUV laser diodes on single-crystal AlN substrate. (22nd December 2021) - Kushimoto, Maki; Zhang, Ziyi; Honda, Yoshio; Schowalter, Leo J.; Sasaoka, Chiaki; Amano, Hiroshi
Abstract: The presence of hexagonal-pyramid-shaped hillocks (HPHs) in AlGaN epitaxial films affects device characteristics; this effect is significant in DUV laser diodes (LDs) on AlN substrates, where the presence of HPHs under the p-electrode increases the threshold current density and inhibits the lasing. In this study, we investigated the difference between the lasing characteristics of LDs with and without HPHs. It was found that in the presence of HPHs, the threshold excitation power density increased and the slope efficiency decreased by optical excitation. To investigate the cause of these phenomena, we performed structural, optical, and electrical analyses of the HPHs. Various imaging techniques were used to directly capture the characteristics of the HPHs. As a result, we concluded that HPHs cause the degradation of LD characteristics due to a combination of structural, optical, and electrical factors.